2009
DOI: 10.1002/adfm.200800790
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Photorefractivity of Poly(N‐vinylcarbazole)‐Based Composites through Electric‐Field Treatments and Ionic Liquid Doping

Abstract: It is shown that the photorefractive (PR) performance of polymer composites based on poly(N‐vinylcarbazole) can be improved when samples are subjected to an electric field for a certain time, i.e. conditioned, previous to the PR characterization. It is also found that for conditioned samples the addition of an organic ionic liquid to the PR composition allows to obtain PR effect without the need of using a sensitizer. The typical electric field treatment time at room temperature and at a field of 20 V µm−1 is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Therefore, in an effort to assess the effectiveness of the photosensitizer, the σ p and σ d were measured and are presented as a function of the E in Figure . It is noted that in this study the σ p , and σ d traces were similar to those observed for other PVK-based composites . Specifically, in the measurement of σ d , the current decreased with time until a steady state was achieved; however when illuminated, the current was observed to increase until a steady state was obtained.…”
Section: Results and Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Therefore, in an effort to assess the effectiveness of the photosensitizer, the σ p and σ d were measured and are presented as a function of the E in Figure . It is noted that in this study the σ p , and σ d traces were similar to those observed for other PVK-based composites . Specifically, in the measurement of σ d , the current decreased with time until a steady state was achieved; however when illuminated, the current was observed to increase until a steady state was obtained.…”
Section: Results and Discussionsupporting
confidence: 84%
“…For these characterizations, the samples have undergone extensive preconditioning (i.e., subjection to E as well as illumination) prior to any measurements. Because of this preconditioning it is anticipated that polarization currents attributable to the orientation of the AODCST or any contribution from the migration of ionic impurities will be negligible . As such, steady state currents were easily achieved in a matter of minutes.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the FWM techniques as well as the photocurrent experiments, fresh samples that were not exposed to either an external field or light illumination were used. A constant external field of 30 V/m was applied for 30 min before the measurements to reduce the effect of dark current including mobile charges such as ionic ones [32]. The pumping duration for the samples was 1 s in both the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…From the standpoint of chemistry, the most important contribution to the field of PR material research has been the search of novel and more efficient sensitizing molecules. Besides reports on PR response without the use of a sensitizing agent,101, 102 the sensitizer is understood to have a major impact with regard to the field‐dependent steady‐state and, even more pronounced, dynamic performance of the composites.…”
Section: Methodsmentioning
confidence: 99%